2021
DOI: 10.1371/journal.pone.0261246
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and tuberculosis, a systematic review and meta-analysis with sensitivity analysis for studies comparable for confounders

Abstract: Introduction Meta-analyses conducted so far on the association between diabetes mellitus (DM) and the tuberculosis (TB) development risk did not sufficiently take confounders into account in their estimates. The objective of this systematic review was to determine whether DM is associated with an increased risk of developing TB with a sensitivity analyses incorporating a wider range of confounders including age, gender, alcohol consumption, smoke exposure, and other comorbidities. Methods Pubmed, Embase, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 81 publications
1
12
0
1
Order By: Relevance
“…Evidence on the association between DM and the risk of LTBI was still limited. Previous meta-analyses had shown that DM was associated with the risk of TB ( 15 , 16 ), yet the association between DM and LTBI was still unclear. Recently, global attention to the association between DM and the risk of LTBI has increased, and there were more observational studies published in recent years, especially for cohort studies ( 17 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the association between DM and the risk of LTBI was still limited. Previous meta-analyses had shown that DM was associated with the risk of TB ( 15 , 16 ), yet the association between DM and LTBI was still unclear. Recently, global attention to the association between DM and the risk of LTBI has increased, and there were more observational studies published in recent years, especially for cohort studies ( 17 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis published in 2021 with a search up to 2020 [ 26 ] found 49 studies reporting on the risk of TB in adults with diabetes mellitus versus a range of comparator groups. The overall pooled odds ratio estimate of active TB from the 49 studies was 2.33 (95% CI 2.00–2.71), with high between-study heterogeneity (I 2 =94.2%) ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis published in 2017 with a search up to 2015 [ 24 ] included many of the same studies captured in the aforementioned 2021 meta-analysis [ 26 ] and presented an overall pooled summary estimate of 2.00 (95% CI 1.78–2.24) combining any measure of association (odds ratio/risk ratio/IRR/hazard ratio (HR)) from 44 studies, with high between-study heterogeneity (I 2 =90.5%). Similar estimates were obtained across subgroup analyses by design and measure of association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, 15% of active TB cases are estimated to be attributable to DM (5); DM is associated with an increased risk of TB disease (6). We recently reported that DM in persons with TB disease increased the odds of M. tuberculosis (Mtb) transmission to close contacts (7).…”
Section: Introductionmentioning
confidence: 99%